An experimental study of the stability of the bitwise data hiding method, relative to attacks, based on affine transformations - Ковтун, Владислав Юрійович; Кінзерявий, Олексій Миколайович (Ukrainian Information Security Research Journal, 2015)
In this work an experimental study was conducted toverify the stability of the bitwise data hiding method inthe structure of vector image, relative to attacks, based onaffine transformations. The arbitrarily SVG image, in thestructural composition of which were the commands ofconstructing Bezier curves, was chosen for theexperiment. In one of these curves, by its gradual separationinto a visually identical aggregate of segments, werehiding data of different sizes. The various affine transformationssuch as permutation, rotation, offset along theabscissa and ordinate, proportional and non-proportionalscaling were gradually performed over received steganocontainer.The received results for the transformationof the steganocontainer showed that the consideredmethod of hiding data in vector images providesresistance to attacks based on affine transformations.